DISCOVERY LEARNING MODEL EBOOK DEVELOPMENT ON ECOSYSTEM MATERIALS FOR DISTANCE LEARNING - Yunita Kurniasih; Diana Vivanti Sigit; Tri Handayani Kurniati (EDUSAINS, 2021)
DISCOVERY LEARNING MODEL EBOOK DEVELOPMENT ON ECOSYSTEM MATERIALS FOR DISTANCE LEARNINGAbstractThe covid-19 pandemic requires students to study from home, so appropriate teaching materials such as ebooks are needed. The purpose of this research is to develop an ebook discovery learning model for ecosystem materials to support distance learning. The method used is research and development through six stages, namely data collection, planning, initial product creation, small-scale trials, revisions, and large-scale trials. The results of the research are in the form of an ebook on discovery learning model ecosystem materials that are suitable for students needs. The ebook was validated by media experts, material experts, and linguists then tested on students with small and large scale numbers. Samples were taken using a purposive sampling technique involving 10 students for a small scale and 60 students for a large scale. Data collection techniques using questionnaires and interviews. The results of the validation test by media experts were 84% (very good), material and language experts were 89,3% (very good). The results of the student response questionnaire to the use of ebooks are 87% in the high category. These results show that the ebook discovery learning model ecosystem material developed is very good for use by students during distance learning.AbstrakPandemi covid-19 mengharuskan siswa belajar dari rumah, sehingga dibutuhkan bahan ajar yang sesuai seperti ebook. Tujuan dari penelitian ini adalah mengembangkan ebook model discovery learning materi ekosistem untuk mendukung pembelajaran jarak jauh. Metode yang digunakan yaitu research and development melalui enam tahapan, yaitu pengumpulan data, perencanaan,  pembuatan produk awal, uji coba skala kecil, revisi, dan uji coba skala besar. Hasil penelitian berupa ebook materi ekosistem model discovery learning yang sesuai dengan kebutuhan siswa. Ebook divalidasi oleh ahli media, ahli materi, dan ahli bahasa kemudian diujicobakan pada siswa dengan jumlah skala kecil dan skala besar. Sampel diambil menggunakan teknik purposive sampling yang melibatkan 10 orang siswa untuk skala kecil dan 60 siswa untuk skala besar. Teknik pengumpulan data menggunakan kuesioner dan wawancara. Hasil uji validasi oleh ahli media sebesar 84% (kategori sangat baik), ahli materi dan bahasa sebesar 89,3% (kategori sangat baik). Hasil angket respon siswa terhadap pemakaian ebook sebesar 87% dengan kategori tinggi. Hasil ini menunjukkan ebook materi ekosistem model discovery learning yang dikembangkan sangat baik untuk digunakan oleh siswa saat pembelajaran jarak jauh.